2013
DOI: 10.3109/09537104.2013.782484
|View full text |Cite
|
Sign up to set email alerts
|

Value of vanin-1 assessment in adult patients with primary immune thrombocytopenia

Abstract: The diagnosis of primary immune thrombocytopenia (ITP) is clinical and cannot be established by any specific laboratory assay. Perhaps the best diagnostic study is assessment of the patient's response to ITP therapy. Oxidative stress-related pathways were among the most significant chronic ITP-associated pathways. Overexpression of VNN1 gene, an oxidative stress sensor in epithelial cells, was most strongly associated with progression to chronic ITP. To address this issue, we tested the hypothesis that blood v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…A total of 20 patients with ITP at the onset stage, 40 patients with chronic ITP, and 30 healthy matched controls were enrolled in this study. He found that, 15.6% were males and 84.4% were females, showing a female predominance, with age range of 18-50 years with mean of 31.8 years, which was in agreement with the results of (7,8,9) All these studies were performed on patients with ITP and showed that ITP among adults affects females more than males, with no specific age predominance. On comparing our three groups, we found no statistically significant difference between them.…”
Section: )supporting
confidence: 78%
“…A total of 20 patients with ITP at the onset stage, 40 patients with chronic ITP, and 30 healthy matched controls were enrolled in this study. He found that, 15.6% were males and 84.4% were females, showing a female predominance, with age range of 18-50 years with mean of 31.8 years, which was in agreement with the results of (7,8,9) All these studies were performed on patients with ITP and showed that ITP among adults affects females more than males, with no specific age predominance. On comparing our three groups, we found no statistically significant difference between them.…”
Section: )supporting
confidence: 78%
“…Phosphorylcholine, a CRP ligand present on cell surfaces, was exposed after antibody-induced oxidative stress. Oxidative stress induced by ITP autoantibodies has also been shown in two separate studies on ITP ( 217 , 218 ) and appears to be a suitable biomarker for ITP ( 219 ). Additionally, the pathophysiological role of reactive oxygen species has long been implied in a model of HIV-initiated ITP ( 64 , 65 , 67 ).…”
Section: Pathways Involved In Platelet Clearancementioning
confidence: 77%
“…Despite these highly variable estimates in normal humans, Vanin-1 levels in dolphins appear to be 20–1000 times higher than human. Because reported human serum measurements from the same ELISA manufacturer were incongruent 44 45 with estimates based on proteomic analysis 25 , we performed a product ion scan targeting the homologous human Vanin-1 peptide utilized to measure dolphin Vanin-1 in this study. No signal for the human Vanin-1 peptide was found in normal pooled human serum (data not shown) suggesting human Vanin-1 levels are indeed low and likely to be in the range of ng/ml.…”
Section: Discussionmentioning
confidence: 99%